Advergaming ve Marka İlişkisi - Ilgın, Hicran Özlem (The Turkish Online Journal of Design Art and Communication, 2013)
In 1994, internet advertising which is emerged by the telecommunication company AT & T by giving out a banner advertisement to an internet magazine called “HotWired”; with the development of information technology today and effective presence of the new media which is one of the content of the concept of "advergaming" surrounding every moment of our lives, has reached a different dimension. At the beginning, we find applications of advergame in the form of simple games designed for product advertising as they create a positive impact on the target audience in a short time, with their lower costs and the capabilities of creating brand awareness with their entertaining features and their data bank sources, they attract the attention of brands. In this context, the main area of the study is the concept of new media, the internet advertising, and as a result, the emergence of the concept of advergaming and its innovations for the world of brands will be discussed.
Keywords: Advergaming; Reklam; Brand; Marka